High-Altitude Agro-Pastoralism in the Kyrgyz Tien Shan: New Excavations of the Chap Farmstead (1065–825 cal b.c.). (2nd January 2020) - Motuzaite Matuzeviciute, Giedre; Tabaldiev, Kubatbek; Hermes, Taylor; Ananyevskaya, Elina; Grikpedis, Mindaugas; Luneau, Elise; Merkyte, Inga; Rouse, Lynne M.
ABSTRACT: The highlands of Central Asia posed considerable challenges to early agriculturalists, yet the processes of human subsistence strategies there remain poorly understood. In this paper, we present results from the excavation of the Chap in Kyrgyzstan. The recovery of a rich macrobotanical assemblage consisting of several crop species and crop processing debris, together with skeletal remains of pastoral livestock, indicate a localized agro-pastoral complex at 2000 masl dating to 1065–825 cal b.c . Aerial photogrammetry, magnetometry, and topographic modeling reveal local irrigation systems, while stone artifacts are linked with cultivation and crop processing. Furthermore, the ceramic assemblage reveals a local production tradition and stylistic similarities with communities of neighboring regions. Overall, data from Chap contribute to a new understanding of human ecology and agricultural development in the mountains of Central Asia, suggesting that domesticated plants and animals were integral for the intensive occupation of high-elevation valleys in Central Asia.